PENGUATAN KETAHANAN EKONOMI PESANTREN MELALUI PEMBERDAYAAN KEWIRAUSAHAAN BERBASIS HIDROPONIK: PENDEKATAN PENGEMBANGAN KOMUNITAS BERBASIS ASET DI KLATEN, INDONESIA - Nurohman, Yulfan Arif; Khoiriyah, Rahmawati; Hasyim, Fuad; Ahzar, Fahri Ali (Sekolah Tinggi Ilmu Ekonomi AMA, 2026)
Indonesia is the country with the largest Muslim population globally and has over 40,000 Islamic boarding schools (pesantren). However, most of these schools face challenges in financial management and economic sustainability. This study, however, examines the strategic role of Islamic boarding schools in providing Islamic education to the community. This study conducted an economic empowerment program for Islamic boarding schools through hydroponic entrepreneurship training to strengthen their economic resilience. The program was implemented at Islamic boarding schools in Klaten using an Asset-Based Community Development (ABCD) approach. This approach emphasizes the importance of local assets and active participant involvement. The program consisted of four stages: needs assessment, participatory planning, entrepreneurship training, mentoring, and outcome evaluation. These activities were supported by observation, interviews, and participant evaluation methods to adjust the community service program. Findings indicate an increase in students' entrepreneurial knowledge, technical skills, and economic awareness after participating in the program. The learning provided hands-on experience in hydroponic practices, increasing engagement and facilitating the development of entrepreneurial competencies. Mentoring ensured the program met its targets and determined its sustainability. The results of this study highlight that integrating entrepreneurship education with locally adaptable practical innovations can foster sustainable economic models in religious educational institutions, positioning Islamic boarding schools as agents of inclusive economic development.